Micoteca da Universidade do Minho (MUM): a portuguese culture collection - Simões, Marta Filipa Jesus Freitas (2010)
[Excerpt] Micoteca da Universidade do Minho - MUM is a mycological culture collection that exists since 1996 and is hosted by the Biological Engineering Research Centre (www.deb.uminho.pt), a centre of excellence integrated in the Institute for Biotechnology and Bioengineering (IBB - www.ibb.pt). The mission of MUM is to provide the highest quality services to its customers, collecting, maintaining and supplying fungal strains and their associated information for teaching and research in biotechnology and life sciences, and to be a centre of knowledge, information and training in mycology, operating at a global level and under national and international regulations [1,2]. (...)